2009
DOI: 10.1111/j.1432-2277.2009.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after 1000 heart transplantations in six different eras of innovation in a single center

Abstract: Summary The objective of this study was to evaluate long‐term outcomes of cardiac transplantation (HTx) in different eras of innovation at a single center during a period of 27 years. We performed a retrospective analysis of 960 cardiac allograft recipients (40 re‐HTx) between 1981 and 2008. The results of six different eras based on milestones in HTx were analysed: Era 1: the early years (n = 222, 1981–1992); era 2: introduction of inhalative nitric oxide, prostanoids, University of Wisconsin solution (UW) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The finding that early outcomes have improved similarly among racial groups adjusted for these risk factors suggests that advances in recipient selection, in the care of patients awaiting a heart transplant, in peri-operative care of transplant recipients and in immune suppression, which have contributed to improvement in early survival after heart transplantation, 3-5 have been implemented widely among centers and have benefited the racial groups equally. Several risk factors for early mortality such as VAD support, PVR>3, anti-HLA antibodies>10% and administration of intravenous antibiotics <2 weeks prior to transplant were more prevalent in black recipients and residual confounding with respect to these risk factors could have contributed to their worse early outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that early outcomes have improved similarly among racial groups adjusted for these risk factors suggests that advances in recipient selection, in the care of patients awaiting a heart transplant, in peri-operative care of transplant recipients and in immune suppression, which have contributed to improvement in early survival after heart transplantation, 3-5 have been implemented widely among centers and have benefited the racial groups equally. Several risk factors for early mortality such as VAD support, PVR>3, anti-HLA antibodies>10% and administration of intravenous antibiotics <2 weeks prior to transplant were more prevalent in black recipients and residual confounding with respect to these risk factors could have contributed to their worse early outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although black and Hispanic transplant recipients in the current study were three times as likely to have Medicaid insurance as white recipients, the reported race effects were seen after adjusting for insurance. Given that newer immune suppression agents (such as mycophenolate mofetil, tacrolimus and sirolimus) reduce rejection rates, prevent progression of cardiac allograft vasculopathy and improve graft and patient survival in heart transplant recipients, 5, 20-23 our finding that a similar or higher percentage of black and Hispanic transplant recipients (vs. white recipients) received maintenance mycophenolate and tacrolimus in all eras makes it unlikely that the lack of improvement in longer-term survival in these recipients was due to a disparity in choice of immune suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,12 According to the ISHLT data, female donor hearts have a lower risk for the development of transplant vasculopathy 5 years after HT. 6 Although hearts from male donors older than 35 years of age have been reported to be at a risk to develop transplant vasculopathy, probably based on pre-existing coronary lesions, 6 Hiemann et al found stenotic microvasculopathy in myocardial biopsies equally in men (38%) and women (39%).…”
Section: Discussionmentioning
confidence: 99%
“…In sporine had triggered the breakthrough of heart transplantation in the 1980s, the development of tacrolimus, another calcineurin inhibitor (CNI), opened up the possibility of further refining immunosuppression. Administration of tacrolimus could be shown to reduce the frequency of acute rejection episodes and the incidence of chronic allograft v asculopathy [10]. Also, chronic renal disease developed less frequently under immunosuppression based on tacrolimus as compared to cyclosporine [11].…”
Section: Introductionmentioning
confidence: 99%